Integration of interactive computer simulations in teaching and learning chemical reaction: Students' performance and concept retention - Jane Batamuliza; Gonzague Habinshuti; Jean Baptiste Nkurunziza (OmniaScience, 2024)
This current study presented the effects of interactive computer simulations on students' performance and concept retention in the unit of chemical reactions. Purposive sampling was used to select four schools with 320 students, in Kayonza district Rwanda. The Achievement test on chemical reactions was developed, validated, and checked for reliability. The participating students were in grade 8. The collected data was analyzed in MS Excel and SPSS. The independent sample t-tests were computed to compare the groups and reveal the effectiveness of interactive computer simulations. After the intervention, the experimental groups' post-test means achievement scores of (8.67) were higher than that of the control groups (6.69). The difference between the two mean scores was statistically significant: t (318) = 6.3, p= .000. The experimental group also had higher mean post-retention-test scores of (M = 8.07, α = .29) than that of the control group (M =5.58, α = .19) which was statistically significant at t (318) = 7.28, p = .000. Therefore, it is concluded that interactive computer simulations enhance students' performance and improve their concept retention. The study recommends that simulations should be used to supplement the teaching and learning of chemistry and other science subjects in general.